Informed consent guidelines for ionising radiation examinations: A Delphi study. Issue 1 (February 2020) - Younger, C.W.E.; Douglas, C.; Warren-Forward, H.
Abstract: Introduction: Informed consent for ionising radiation medical imaging examinations is currently undertaken inconsistently in Australian radiographic practice. There is no uniform informed consent process, and opinions vary about how it should be undertaken, and by whom, if indeed it needs to be undertaken at all. To ensure that patients' rights are maintained, the informed consent process must be consistent, proactive in the provision of information, and must empower the patient to formulate and ask questions about their care, and to make voluntary decisions. Methods: The Delphi technique utilises a group of experts whose individual responses are used to create a collective consensus on a process. This ten-expert (five radiographer, five radiologist) Delphi study examined a basic modelling of the process of informed consent for ionising radiation medical imaging examinations and made recommendations for an ideal process. Results: A series of consensus statements were developed, seeking to rectify areas of the process that were inconsistent, unclear, or ethically unsound. These statements were then considered alongside current codes of professional practice, and Australian law on the duty of disclosure. A model of the ideal process was then developed using these consensus statements and adhering to codes of practice. Conclusion: The final process model has a continuity of care and a continuity of information provision. The model eliminates the radiographer as a delegatee, and emphasises physician involvement. The referrer and the radiologist have a shared responsibility of providing risk disclosure information. Implications for Practice: For a non-pregnant adult, the ionising radiation dose from conventional radiography is considered insignificant, and does not require risk disclosure, ameliorating the time commitment needed for the process.